2021
DOI: 10.1080/19490976.2021.1979877
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between gut bacteria and the yeast Candida albicans

Abstract: The fungus Candida albicans is a ubiquitous member of the human gut microbiota. Hundreds or thousands of bacterial taxa reside together with this fungus in the intestine, creating a milieu with myriad opportunities for inter-kingdom interactions. Indeed, recent studies examining the broader composition – that is, monitoring not only bacteria but also the often neglected fungal component – of the gut microbiota hint that there are significant interdependencies between fungi and bacteria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…Similarly, the fungal community also evolved significantly after supplementation of fermented and hydrolyzed AXOS with an increase in Candida relative abundance and a decrease in Issatchenkia , while the intake of non-hydrolyzed/non-fermented AXOS did not produce relevant changes. This observed reshaping of both bacterial and fungal communities within the PC is not surprising since a large body of literature exists showing how bacteria interplay fungal traits in gut ecosystems and vice versa [ 25 ]. In any case, this study highlights how the preliminary fermentation by lactic acid bacteria and the hydrolyzation of cereal-based flours containing AXOS had the capacity to address the microbiome modulation within the PC tract in a different way compared to that given by non-fermented/non-hydrolyzed formulation.…”
Section: Discussionmentioning
confidence: 80%
“…Similarly, the fungal community also evolved significantly after supplementation of fermented and hydrolyzed AXOS with an increase in Candida relative abundance and a decrease in Issatchenkia , while the intake of non-hydrolyzed/non-fermented AXOS did not produce relevant changes. This observed reshaping of both bacterial and fungal communities within the PC is not surprising since a large body of literature exists showing how bacteria interplay fungal traits in gut ecosystems and vice versa [ 25 ]. In any case, this study highlights how the preliminary fermentation by lactic acid bacteria and the hydrolyzation of cereal-based flours containing AXOS had the capacity to address the microbiome modulation within the PC tract in a different way compared to that given by non-fermented/non-hydrolyzed formulation.…”
Section: Discussionmentioning
confidence: 80%
“…The change of ITS/16S diversity ratio reflects the change of fungus-bacterial microbiota balance. A recent study showed that gut fungal and bacterial microbiota are interdependent, especially the interaction of gut bacteria microbiota with Candida albicans ( Pérez, 2021 ). Another study in ankylosing spondylitis also found that Candida was associated with a variety of bacteria ( Li et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing fascination of how C. albicans interacts with bacterial species within complex interkingdom communities [ 31 , 56 , 69 , 70 ]. These studies have been instrumental in furthering our understanding of how this opportunistic yeast co-operates, or otherwise, with key bacterial species.…”
Section: Discussionmentioning
confidence: 99%